Frequency upconversion involving triads and quartets of ions in a Pr3+/Nd3+ codoped fluoroindate glass - Falcão-Filho, Edilson L.; Araújo, Cid B. de; Messaddeq, Younes [UNESP] (AIP Publishing, 2002)
Frequency upconversion (UC) processes involving energy transfer (ET) among Nd 3+ and Pr 3+ ions in a fluoroindate glass are reported. In a first experiment, the excitation of Pr 3+ [transition 3H 4→ 1D 2] and of Nd 3+ [transition 4I 9/2→( 2G 7/2+ 4G 5/2)] was achieved with a dye laser operating in the 575-590 nm range. In a second experiment, the Nd 3+ ions were excited with the second harmonic of a Nd: YAG laser at 532 nm. The ET processes leading to UC in both experiments were studied by monitoring the blue fluorescence decay at 480 nm due to the transition 3P 0→ 3H 4 in Pr 3+. In the more relevant UC process, quartets of ions (Nd-Nd-Pr-Pr) are excited due to absorption of three laser photons by two Nd 3+ ions which transfer their energy to two Pr 3+ ions. Each Pr 3+ ion promoted to the 3P 0 level decays to the ground state emitting one photon in the blue region. This conclusion was achieved investigating the dependence of the UC fluorescence intensity as a function of laser intensity, samples concentrations, and temporal behavior of the UC signal. Other UC processes involving nonisoionic groups of three ions are also reported. © 2002 American Institute of Physics.
Keywords: Blue fluorescence; Co-doped; ET process; Fluorescence intensities; Fluoroindate glass; Frequency up-conversion; Laser intensities; Laser photons; ND : YAG lasers; Second harmonics; Temporal behavior; Dye lasers; Energy transfer; Experiments; Glass; High energy physics; Neodymium; Neodymium lasers; Photons; Ions